THYROID FUNCTION ABNORMALITIES AND LIPID PROFILE OF PATIENTS WITH METABOLIC SYNDROME: A CROSS-SECTIONAL STUDY - TASO BEYONG,; RATAN RAM, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective was to study the prevalence of thyroid function abnormalities and lipid profile in cases with metabolic syndrome. Methods: We conducted this observational cross-sectional study of 80 patients with metabolic syndrome to analyze their thyroid functions and lipid profile. The study was conducted in the department of general medicine of a tertiary care medical institute. Individuals fulfilling the National Cholesterol Education Program Adult Treatment Panel III criteria for metabolic syndrome were included in this study on the basis of a predefined inclusion and exclusion criteria. Demographic details were noted. A detailed history was taken and a clinical examination was done. Thyroid function test and lipid profile were done in all cases. The presence of thyroid function and lipid profile abnormalities was analyzed. Statistical analysis was done using SPSS 21.0 software and p<0.05 was taken as statistically significant. Results: Out of these 80 cases, there were 43 (53.75%) males and 37 (46.25%) females with a M: F ratio of 1:0.86. The mean age of male and female patients was comparable with no statistically significant difference (p=0.3739). Analysis of thyroid functions showed that 48.75% of patients were euthyroid, 35% had subclinical hypothyroidism, and 16.25% had clinical hypothyroidism. Notably, euthyroid patients had more stable lipid profiles with a total cholesterol mean of 189.45 mg/dL and triglycerides at 162.65 mg/dL. In contrast, patients with clinical hypothyroidism showed significant lipid disturbances, including total cholesterol of 249.87 mg/dL and triglycerides at 274.42 mg/dL. Conclusion: Thyroid dysfunction and dyslipidemia are common occurrence in patients with metabolic syndrome. Also, individuals with metabolic syndrome, particularly if they have coexistent thyroid dysfunction are at increased risk of developing significant dyslipidemia. It is therefore important to monitor thyroid functions and lipid profile of individuals with metabolic syndrome.